The Influence of Posterior Class II Composite Restoration Location and Techniques on Marginal Sealing - Mishel Haddad; Diva Lugassy; Mohana Barhum; Tamar Brosh; Shlomo Matalon (Dentistry Journal)
Background/Objectives: The success of treatment and prevention for secondary caries hinges significantly on the techniques employed in Class II composite restoration. Additionally, the location of the restored tooth within the oral cavity has emerged as a potential factor determining the quality of the restoration. A comprehensive understanding of these interrelated variables is crucial for advancing the efficacy and durability of dental composite restorations. The aim of this study was to assess how various restoration techniques and the specific location of the tooth restoration in the oral cavity affect marginal sealing, verified by the gap created in the tooth–restoration interface. Methods: Sixty extracted human teeth that had been indicated for orthodontic extraction were collected and embedded into a custom-made holder that was located in one of the four quadrants of a laboratory phantom head. Class II resin composite restorations, using flowable and packable composites, were performed on all teeth using two techniques: Pre-cure and Co-cure. The aging of the restored teeth was conducted using cyclic loading and thermocycling. After aging, the teeth were examined under a scanning electron microscope to measure the gap within the tooth–composite interface. Kolmogorov–Smirnov tests were used to assess the data distribution. Unpaired T-tests were employed to compare the mean gaps between the Pre-cure and Co-cure techniques. Additionally, unpaired T-tests were utilized to compare the mean gaps between the mesial and distal parts of the teeth. The Kruskal–Wallis test was used to compare the mean gaps among the four quadrants. The statistical significance was set at p = 0.05. Results: No significant difference in the gaps between the Pre-cure and Co-cure techniques was found (p = 0.212). The tooth’s location did not generally affect the restoration’s gap interface (p = 0.136). Conclusions: Flowable composites aid in restoring the deep margins of Class II composite restoration. Thus, the potential for further microleakage is similar for both the Pre-cure and Co-cure restoration techniques. The marginal seal of Class II composite restorations is effective when using both Pre-cure and Co-cure techniques, and the restoration site within the oral cavity does not significantly influence the tooth–composite interface seal.